Manajemen Sekolah Penggerak Berbasis Teknologi Informasi untuk Pemenuhan Standar Digitalisasi Sekolah Menengah atas di Kota Lubuklinggau - Prananosa, Ahmad Gawdy; Tamri, Tamri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the management of schools based on information technology to meet the standards of digitalization of senior high schools in Lubuklinggau City. This study was designed with an educational action research scheme. The subjects of the study were driving teachers, principals, students, TU staff and school supervisors. Data collection techniques include; interviews, documentation and observation, while data analysis techniques use qualitative analysis. The results of the study, Management of driving schools based on information technology starts from making policies, including; 1) mechanisms, 2) implementation, and 3) evaluation, after the next policy prepares facilities, namely 1) procurement, 2) use, and 3) maintenance. In addition, it also forms an organizational structure, consisting of; 1) implementation, 2) coordination, and 3) monitoring and evaluation. Then the management of financing, namely: 1) planning, 2) implementation, and 3) audit, and finally the supervisory activities include; 1) planning, 2) mechanisms, and 3) implementation. Conclusion, the management of driving schools based on information technology to meet school digitalization standards, namely making policies, preparing facilities, forming organizational structures, financing, and supervision. Keywords: School Digitalization, School Management, Driving School, Information Technology